Development Strategy of Buluballea Agritourism Area in Pattapang Village, Tinggimoncong District, Gowa Regency, South Sulawesi - Andi Aslam Nugraha Nur; Bagyo Yanuwiadi; Sri Sudaryanti (Jurnal Penelitian Pendidikan IPA, 2025)
Utilization of local resources can be enhanced through sustainable agritourism that integrates agriculture with tourism. Agritourism provides educational value, recreational experience, and business opportunities in the agricultural sector. The Buluballea area in Tinggimoncong District, Gowa Regency, has strong potential for agritourism due to its mountainous terrain, cool climate, and horticultural production center. Surrounding attractions include cultural sites such as the Bulu’Tana Traditional House, natural destinations like Takapala Waterfall, Malino Forest, Mount Bawakaraeng, and artificial attractions such as Malino Highland Tea Plantation.Research conducted between March–June 2024 involved 100 respondents selected via purposive sampling. Data analysis used quantitative descriptive methods, MDS to assess sustainability, and SWOT with IFAS and EFAS matrices for development strategy formulation. Findings show Buluballea’s agritourism potential is highly promising and positively received by the community. Agritourism is expected to enhance tourism diversity, strengthen the local economy, and develop cultural and agricultural commodities. Development strategies include leveraging natural, cultural, and local commodities; community training; branding and digitalization; as well as institutional strengthening and sustainable management to address environmental, climatic, and destination competitiveness challenges.